2019
DOI: 10.1111/acel.12927
|View full text |Cite
|
Sign up to set email alerts
|

Systemic clearance of p16INK4a‐positive senescent cells mitigates age‐associated intervertebral disc degeneration

Abstract: Rationale Age‐related changes in the intervertebral discs are the predominant contributors to back pain, a common physical and functional impairment experienced by older persons. Cellular senescence, a process wherein cells undergo growth arrest and chronically secrete numerous inflammatory molecules and proteases, has been reported to cause decline in the health and function of multiple tissues with age. Although senescent cells have been reported to increase in intervertebral degeneration (IDD), it is not kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(129 citation statements)
references
References 44 publications
4
124
1
Order By: Relevance
“…Alterations in genes that are associated with inflammatory processes, response to stress, cell differentiation, cell metabolism and cell division were shared. Recent aging studies supports the importance of inflammation and metalloproteases secretion (Novais et al, 2019; Tessier et al, 2019), cell differentiation (Mohanty, Pinelli, Pricop, Albert, & Dahia, 2019) and cell cycle (Novais et al, 2019; Patil et al, 2019) in disc health. Moreover, comparison of altered pathways in LG/J aging with changes seen between old LG/J versus BL6, suggested that 23M LG/J mice evidence similar changes in cell differentiation/ossification, inflammation, cell death, phosphate metabolism along with altered DNA repair and immune response‐related processes.…”
Section: Discussionmentioning
confidence: 84%
“…Alterations in genes that are associated with inflammatory processes, response to stress, cell differentiation, cell metabolism and cell division were shared. Recent aging studies supports the importance of inflammation and metalloproteases secretion (Novais et al, 2019; Tessier et al, 2019), cell differentiation (Mohanty, Pinelli, Pricop, Albert, & Dahia, 2019) and cell cycle (Novais et al, 2019; Patil et al, 2019) in disc health. Moreover, comparison of altered pathways in LG/J aging with changes seen between old LG/J versus BL6, suggested that 23M LG/J mice evidence similar changes in cell differentiation/ossification, inflammation, cell death, phosphate metabolism along with altered DNA repair and immune response‐related processes.…”
Section: Discussionmentioning
confidence: 84%
“…These markers were positively correlated with the expression of matrix metalloproteases including matrix metalloproteinase 13 (MMP13) and a disintegrin and metalloproteinase with thrombospondin motifs 5 (ADAMTS5) . Recently, Patil et al demonstrated the causal relationship between cellular senescence and age‐related IDD using the p16‐3MR transgenic mouse model in which p16‐positive senescent cells can be selectively eliminated by treatment with ganciclovir . The aging mice (age: 1 year) treated with ganciclovir showed decreased levels of catabolic factors along with improved histological features of IDD at age 2 years compared with control mice, indicating that cellular senescence has a direct impact on IDD development.…”
Section: Pathomechanism and Histological Features Of Human Idd And Lmentioning
confidence: 99%
“…Moreover, the mRNA expression of senescence marker genes, P53, P21 and P16 were increased in the senescent AML12 cells compared to control AML12 cells (Figure 1d). Similarly, the expression of these genes also was increased in livers from old mice (100-108 week age) compared to those from young mice (12)(13)(14)(15)(16)(17)(18)(19)(20) week age) (Figure 1e). Furthermore, multiple H2O2 treatments increased senescence since there was increased activated -Gal (SA -Gal)-positive cells (Figure 2a,b) and H2A.X-positive cells containing condensed chromatin in larger nuclei (Figure 2c,d).…”
Section: Senescence Induction and Validation In Aml12 Cellsmentioning
confidence: 82%
“…Under pathological stress conditions, excessive accumulation of senescence cells in affected tissues adversely affects the tissue's regenerative ability and creates a proinflammatory environment that can resemble various age-related disorders such as Alzheimer's disease, cancer, arthritis, cataracts, osteoporosis, atherosclerosis, hypertension, cardiovascular disease, Type 2 diabetes, and chronic liver disorders [3,5,7,[9][10][11][12]. Targeting senescent cells has the potential to delay age-associated disorders and/or reverse pathological metabolic phenotypes [3,[13][14][15][16]. Recent studies in the liver show that inducing hepatocyte senescence promotes fat accumulation and hepatic steatosis in vitro and in vivo [17].…”
Section: Introductionmentioning
confidence: 99%